2017
DOI: 10.1111/ans.14121
|View full text |Cite
|
Sign up to set email alerts
|

General surgery primary operator rates: a guide to achieving future competency

Abstract: Background: Competency in surgical training is a topic of much recent discussion, with concern regarding the adequacy of current training schemes to achieve competency. Most programmes use caseload and primary operator rates to assess trainee progression. Some trainees still lack technical competence even when recommended procedural numbers are met. It is possible that current measures of individual's capabilities used in surgical education are outdated. Methods: Logbook data of New South Wales general surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
(15 reference statements)
3
4
0
Order By: Relevance
“…In our study, case volumes and primary operator rates significantly varied according to the operation type. This is similar to another Australian logbook study, reporting on the 10 most common logbook trainee operations in New South Wales, which found that certain operations (cholecystectomy and right hemicolectomy) were associated with poor primary operator rates regardless of trainee seniority.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, case volumes and primary operator rates significantly varied according to the operation type. This is similar to another Australian logbook study, reporting on the 10 most common logbook trainee operations in New South Wales, which found that certain operations (cholecystectomy and right hemicolectomy) were associated with poor primary operator rates regardless of trainee seniority.…”
Section: Discussionsupporting
confidence: 87%
“…This retrospective longitudinal cohort study assessed the experience and autonomy of general surgery trainees in New Zealand in 10 emergency general surgery procedures. The data demonstrated that trainees acquire increasing levels of PO and APO rates during their training, in line with expectations of the training programme and previously published data 15 . This is reflected in the multivariate analysis, demonstrating that for most procedures SET year and case volume per training term are independently associated with reaching the 70% PO and APO thresholds.…”
Section: Discussionsupporting
confidence: 85%
“…Over time, those who had prior experience but were not routinely performing laparoscopic surgery and those without prior experience, were both able to perform laparoscopic surgery with minimum risks. A steep increase in primary operators among local doctors reflected the progression of technical independence, which is essential for long-term sustainability but difficult to attain over a short time period [21]. Furthermore, endoscopic surgical procedures in neurosurgery, gynecology, urology, and orthopedic surgery were phased in by local doctors, supported by the trained nurses and functional equipment.…”
Section: Discussionmentioning
confidence: 99%